1998
DOI: 10.1086/515232
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Interleukin-8 Receptors A and B on Polymorphonuclear Neutrophils from Persons with Human Immunodeficiency Virus Type 1 Disease and Pulmonary Tuberculosis

Abstract: The expression of the two human interleukin (IL)-8 receptors, designated IL-8RA (CXCR-1) and IL-8RB (CXCR-2), on the surface of whole blood polymorphonuclear leukocytes (PMNL) was determined by use of receptor-specific monoclonal antibodies and flow cytometry. Sixteen subjects each were included in 4 study groups: healthy blood donors (ND), patients with pulmonary tuberculosis (TB), human immunodeficiency virus type 1-seropositive patients (HIV), and HIV-1-seropositive subjects with pulmonary tuberculosis (HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 28 publications
3
44
1
Order By: Relevance
“…Based on in vitro experiments, the prevailing view is that neutrophil biology including chemotaxis (4,6), oxidant production, and bacterial killing (4) are affected in HIV infections, such that the innate immune response dominated by these leukocytes is depressed. Although a key feature of the innate immune response is the rapid recruitment of neutrophils, to date a systematic assessment of the potentially affected mechanisms in this multistep process has not been evaluated in lentiviral infections.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Based on in vitro experiments, the prevailing view is that neutrophil biology including chemotaxis (4,6), oxidant production, and bacterial killing (4) are affected in HIV infections, such that the innate immune response dominated by these leukocytes is depressed. Although a key feature of the innate immune response is the rapid recruitment of neutrophils, to date a systematic assessment of the potentially affected mechanisms in this multistep process has not been evaluated in lentiviral infections.…”
Section: Figurementioning
confidence: 99%
“…Although neither HIV nor FIV is thought to infect neutrophils (the primary leukocytes involved in innate immunity), there is a growing body of literature to suggest impairment of neutrophil function from HIV-infected patients in response to bacterial infections despite the preservation of absolute neutrophil counts with advanced immunosuppression. In fact, in the case of HIV, isolated neutrophils have been shown to have decreased oxidant production (3), protease release (3), bacterial killing (4), phagocytosis (5), and chemotaxis (4,6). Although the increased susceptibility to infections in HIV-and FIV-infected patients may be related to impaired antimicrobial functions related to bacterial killing (oxidant production, protease release, phagocytosis), it might also be associated with impaired neutrophil recruitment (rolling, adhesion, or emigration).…”
mentioning
confidence: 99%
“…64 Another study demonstrated significant reduction in the expression of both receptors on neutrophils in persons with pulmonary TB and/or HIV infection. 65 Since neutrophils are known to play a protective nonphagocytic role in the initial host defense mechanisms against M. tuberculosis, 66,67 reduced expression of these receptors could impair the chemotactic response of neutrophils to IL-8 and hence the immune response in mycobacterial infection. These findings also highlight the importance of these receptors in neutrophil functions.…”
Section: Decay Of Ldmentioning
confidence: 99%
“…gp41 has been detected in brain tissues of patients affected by AIDS dementia (22) and Abs recognizing various epitopes of gp41 appear at early stages of HIV infection (61). Moreover, it has been reported that monocytes and neutrophils from HIV-1-infected patients responded poorly to a variety of chemoattractants, including FMLP (62)(63)(64)(65)(66). The interaction of gp41 peptides with FPRs on human basophils might be of clinical relevance in patients with HIV-1 infection.…”
Section: Increasing Evidence Indicates That Human Fc⑀rimentioning
confidence: 99%